Changes of Serum Pyruvate Kinase M2 Level in Patients with Sepsis and Its Clinical Value - Wang L; Tang D; Zhang P (Infection and Drug Resistance, 2023)
Li Wang, Dongling Tang, Pingan Zhang Department of Clinical Laboratory, Institute of Translational Medicine, Renmin Hospital of Wuhan University, Wuhan, Hubei, 430060, People’s Republic of ChinaCorrespondence: Pingan Zhang, Department of Clinical Laboratory, Institute of Translational Medicine, Renmin Hospital of Wuhan University, Wuhan, Hubei, 430060, People’s Republic of China, Tel +86 13971196429, Email zhangpingan927@163.comPurpose: The glucose metabolic reprogramming is an important pathological mechanism in sepsis, which involves a series of enzymes including Pyruvate kinase M2 (PKM2). The purpose of this study is to explore the diagnostic and prognostic value of serum PKM2 in sepsis patients.Patients and Methods: This study recruited 143 sepsis patients, 91 non-sepsis patients, and 65 physical examiners, divided into sepsis group, non-sepsis group, and control group. Measure the serum PKM2 concentration of subjects, collect and analyze clinical and laboratory indicators of all subjects. Independent risk factors were selected by Logistic regression analysis. The area under curve (AUC) was calculated by plotting the receiver operating characteristic (ROC) curve to determine the diagnostic and prognostic value of biomarkers.Results: Compared with non-sepsis and control groups, the serum PKM2 levels in the sepsis group were significantly increased (both P< 0.001). PKM2 was an independent risk factor for sepsis and had the best diagnostic efficacy when combined with procalcitonin, with the AUC value of 0.9352. Patients with high levels of PKM2 were more likely to experience organ damage and had a higher incidence of septic shock. On the 1st and 3rd days of admission, the serum PKM2 levels in the septic shock group were higher than those in the sepsis group (both P< 0.05), with AUC values of 0.7296 and 0.6247, respectively. On the 3rd and 7th days of admission, the serum PKM2 levels in the non-survival group were significantly higher than those in the survival group (both P< 0.001), with AUC values of 0.7033 and 0.8732, respectively.Conclusion: The serum PKM2 levels in sepsis patients are significantly increased and correlated with disease severity and clinical outcomes. PKM2 may be a new diagnostic and prognostic biomarker for sepsis.Keywords: sepsis, PKM2, glucose metabolic reprogramming, diagnosis, prognosis